Adjuvant 5-fluorouracil and leucovorin with or without interferon alfa-2a in colon carcinoma: National Surgical Adjuvant Breast and Bowel Project protocol C-05 - Wolmark, N; Bryant, J; Smith, R; Grem, J; Allegra, C; Hyams, D; Atkins, J; Dimitrov, N; Oishi, R; Prager, D; Fehrenbacher, L; Romond, E; et al. (JNCI : Journal of the National Cancer Institute, 1998)
National Surgical Adjuvant Breast and Bowel Project (NSABP) protocol C-03 showed a benefit from leucovorin (LV)-modulated 5-fluorouracil (5-FU) adjuvant therapy (5-FU + LV) in patients with Dukes' stage B or C carcinoma of the colon. Preclinical and clinical phase I/II data suggested that interferon alfa-2a (IFN) enhanced the efficacy of 5-FU therapy. Accordingly, in NSABP protocol C-05, the addition of recombinant IFN to 5-FU + LV adjuvant therapy was evaluated. Data are presented for 2176 patients with Dukes' stage B or C cancer entered onto protocol C-05 during the period from October 1991 through February 1994. Individuals with an Eastern Cooperative Oncology Group performance status of 0-2 (ranges from fully active to ambulatory and capable of self-care but unable to work), a life expectancy of at least 10 years, and curative resection were stratified by sex, disease stage, and number of involved lymph nodes and were randomly assigned to receive either 5-FU + LV or 5-FU + LV + IFN; the mean time on the study as of June 30, 1997, was 54 months. All statistical tests were two-sided. There was no statistically significant difference in either disease-free survival (5-FU + LV, 69%; 5-FU + LV + IFN, 70%) or overall survival (5-FU + LV, 80%; 5-FU + LV + IFN, 81%) at 4 years of follow-up. Toxic effects of grade 3 or higher were observed in 61.8% of subjects in the group treated with 5-FU + LV and in 72.1% of subjects in the group treated with 5-FU + LV + IFN; fewer patients in the latter group completed protocol-mandated 5-FU + LV therapy than in the former group (77.1% versus 88.5%). The addition of IFN to 5-FU + LV adjuvant therapy confers no statistically significant benefit, but it does increase toxicity.